2011
DOI: 10.1016/j.biomaterials.2011.02.045
|View full text |Cite
|
Sign up to set email alerts
|

Systemic delivery of siRNA to tumors using a lipid nanoparticle containing a tumor-specific cleavable PEG-lipid

Abstract: Previously, we developed a multifunctional envelope-type nano device (MEND) for efficient delivery of nucleic acids. For tumor delivery of a MEND, PEGylation is a useful method, which confers a longer systemic circulation and tumor accumulation via the enhanced permeability and retention (EPR) effect. However, PEGylation inhibits cellular uptake and subsequent endosomal escape. To overcome this, we developed a PEG-peptide-DOPE (PPD) that is cleaved in a matrix metalloproteinase (MMP)-rich environment.In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
122
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 191 publications
(124 citation statements)
references
References 52 publications
1
122
0
1
Order By: Relevance
“…PEGylation enhances the stability and half-life of nano carriers in blood circulation by avoiding recognition and clearance by phagocytic cells of the reticuloendothelial system and is widely used in in vivo applications of nano carriers. As the conventional MEND was composed of a cationic lipid, such as DOTAP, it was necessary to modify the conventional cationic MEND with high amounts of PEG lipids to suppress non-specific electrostatic interactions with internal components, such as negatively charged proteins [22,23,26]. However, it is also known that PEGylation results in a significant loss of gene silencing efficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PEGylation enhances the stability and half-life of nano carriers in blood circulation by avoiding recognition and clearance by phagocytic cells of the reticuloendothelial system and is widely used in in vivo applications of nano carriers. As the conventional MEND was composed of a cationic lipid, such as DOTAP, it was necessary to modify the conventional cationic MEND with high amounts of PEG lipids to suppress non-specific electrostatic interactions with internal components, such as negatively charged proteins [22,23,26]. However, it is also known that PEGylation results in a significant loss of gene silencing efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported on the production of a functional PEG-lipid, PPD, that is affected by matrix metalloproteinases (MMPs), which are secreted by various tumor cells and succeeded in silencing marker gene expression in tumor tissue by the systemic administration of PPD modified MEND [22,23]. In addition, we reported that GALA, a pH-sensitive fusogenic peptide, modified MEND could be applied to an in vivo intratumoral injection model and shGALA, a new shorter version of GALA to improve the pharmacokinetics of the MEND, which was modified to achieve gene silencing in tumor tissue followed by systemic administration [23][24][25][26]. As other strategy, Semple S.C. et.…”
Section: Introductionmentioning
confidence: 99%
“…Particles might be also functionalized with cancer cell targeting ligands, the ligands after cleavage of the PEG shell become exposed, and this can enhance intracellular delivery. Using this methodology, siRNA-loaded nanoparticles improved by approximately 70% the gene-silencing activity in mice bearing fibrosarcomas (34).…”
Section: Enzyme Responsive Delivery Systemsmentioning
confidence: 99%
“…These QD conjugated materials are being applied to a wide variety of biomedical applications, including cancer cell detection, cancer therapy (Fig. 4D), 35 and in vivo imaging of iPS cells (Fig. 4B).…”
Section: Quantum Dots For Ips Cell-based Regenerative Medicine and Gementioning
confidence: 99%
“…[1][2][3][4][5][6][7] In this review article, we mainly overview our research activities, including nanobiodevices for single-cell analysis, [20][21][22][23][24][25] single biomolecule analysis, 19,[26][27][28][29]41,46,50,[54][55][56][57][58] biomarker detections, 23,[30][31][32][33]39,[47][48][49] cancer theranostics, and iPS cell in vivo imaging. [20][21][22][23][24][25][34][35][36][37][38]40,[42][43][44][45]…”
Section: Introductionmentioning
confidence: 99%